Pengaruh Return On Asset,Bopo Dan suku Bunga Terhadap Tingkat Bagi Hasil Deposito Mudharabah Bank Umum Syariah - Rahayu, Putri Ayu; Bustamam, Bustamam (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2016)
This research is an empirical study titled on the Influence of ROA, ROA, and interest rates on the level profit sharing mudarabah Islamic commercial bank deposits. This study aims to determine simultaneously or partial influence of ROA, ROA, and interest rates on the deposits tingkat for mudharabah on sharia banks in Indonesia.The population in this study are all Islamic banks which submit financial statements to the bank Indonesia totaling as many as 10 banks. Due to insufficient sample size or less than 100 then the entire population made in the research sample. This research uses secondary data Islamic commercial bank's financial statements the period 2012-2014 provided websitus Bank Indonesia. Secondary data were then analyzed using multiple linear regression formula with the help of the SPSS.The results of the study explained that ROA positive and significant effect on the level of profit sharing mudarabah deposits in Islamic banks in Indonesia. BOPO and no significant negative effect on the deposits mudaraba tinhgkat for sharia banks in Indonesia. Interest rates positive and significant impact on the level of profit sharing mudarabah deposits sharia banks in Indonesia. Relations ROA, ROA and interest rates to the level of revenue sharing mudarabah deposits is relatively strong.But the role of ROA, ROA and interest rates in affecting the rate for deposits mudarabah Islamic banks in Indonesia is still less dominant in the appeal of other variables. Keywords: ROA, ROA, Interest Rate and Level Sharing Mudharabah deposits